Pengaruh DPK, BI Rate, Dan NPL Terhadap Penyaluran Kredit Modal Kerja Pada BPR Di Provinsi Bali Tahun 2009-2014 - Putra, I Gede Oggy Pratama; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Rural Bank is one of the banks that serve groups of micro, small, and medium enterprises generally Rural Bank location close to the people. This study aimed to determine the effect of third party funds, the BI rate and non-performing loans to the working capital loan portfolio at Rural Bank in Bali province in 2009-2014 by using multiple linear regression analysis technique. The results showed that the third party fund, BI rate and non-performing loans simultaneously significant effect on working capital loans on Rural Bank in Bali province in 2009-2014, while partially obtained that third party funds, the BI rate and non-performing loans positive and significant impact on working capital loans on Rural Bank in Bali Province 2009-2014. Keywords: working capital loans, third-party funds, the BI rate, non-performing loans.
Keywords: working capital loans; third-party funds; the BI rate; non-performing loans